ECOPHYSIOLOGICAL RESPONSES AND ANTIOXIDATIVE DEFENSE OF BANANA PLANTLETS (Musa spp.) TO CHROMIUM (Cr) STRESS IN IN-VITRO CONDITION - Amalia, Lida
Leather tanning industry generates hazardous waste which contains heavy metals chromium (Cr). These wastes are generally dumped directly into the river without any waste treatment in advance. Consequently, it can pollute surrounding water and soil. Cr is known to cause the damage to DNA, proteins, photosynthetic pigments, ultrastructure of chloroplasts and cell membranes. It also inhibits germination, the process of photosynthesis, respiration, cell division and ultimately inhibits the growth and consequently lower plant yields. Therefore, plants that grow in Cr contaminated soil, should have be able to tolerate Cr contamination. Banana cultivars Ambon Lumut (Musa acuminata Colla) and banana cultivars Nangka (M. paradisiaca L.) have been planted by local people in Cr-polluted river side soil. The research is aimed to understand: 1) the ecophysiological responses of banana plantlets to Cr stress by analyzing growth parameters and chlorophyll content, 2) the ability of banana plantlets as Cr accumulator by analyzing the content of Cr in plant tissue, 3) antioxidative defense mechanism of banana plantlets to Cr stress by analyzing proline content, activity of antioxidant enzymes (catalase = CAT and ascorbate peroxidase = APX) and also expression of CAT and APX genes. Observations were done at around IPAL (Waste Water Treatment Plant) Sukaregang Garut by measuring the content of Cr in soil and banana plants that grow in this soil. The next experiment was conducted in-vitro using plantlets of banana cultivars Ambon Lumut and cultivars Nangka from Cr contaminated-soil (Putative Tolerant = PT) and planlets from non-contaminated soil (Non Putative Tolerant = PNT) with 0 ppm, 50 ppm, 100 ppm, 200 ppm and 400 ppm treatments. The results showed that the relative growth rate, the height and the number of banana leaves decreased in line with the increase of Cr concentrations in the medium. The highest relative growth rate was in Ambon Lumut PT banana plantlets (50 ppm Cr treatment), the height and the number of leaves in Nangka PT banana plantlets (50 ppm Cr treatment). The highest Tolerance Index was in Ambon Lumut PT banana plantlets (100 ppm Cr treatment). The highest chlorophyll content was found on Nangka PT banana plantlets (50 ppm Cr treatment). The content of Cr in the banana plantlets was higher with the increase of the concentrations of Cr in the medium. The highest Cr content in the roots of banana plantlets was on Nangka NPT (400 ppm Cr treatment) as well as in the shoots was on Nangka PT banana plantlets (400 ppm iv Cr treatment). The highest Transportation Index was found in Ambon Lumut PT banana plantlets (50 ppm Cr treatment). The highest Bioconcentration Factor was found in Nangka PT banana plantlets (400 ppm treatment). The content of proline in roots and shoots showed no differences, for both cultivars and different concentration. However, the largest proline content found in the leaves of Nangka PT banana plantlets (400 ppm Cr treatment). The enzyme activity of catalase (CAT) and ascorbate peroxidase (APX) in all cultivars showed the differences; whereas, among the different concentrations of Cr there was no difference. Highest CAT enzyme activity in the roots of banana plantlets was found in Nangka PT (200 ppm Cr treatment); while, at the shoots found in Ambon Lumut NPT banana plantlets (50 ppm Cr treatment). Highest APX enzyme activity was found in roots of Nangka NPT banana plantlets (400 ppm Cr treatment); while, at the shoots was on Nangka PT banana plantlets (50 ppm Cr treatment). In PT banana plantlets, the level of CAT gene expression and APX gene was higher than the control. In NPT banana plantlets, the level of CAT gene expression and APX gene were lower. Based on preliminary observations can be known that the soil around IPAL Sukaregang was categorized into Cr contaminated soil and banana plants around IPAL accumulated Cr, especially in the roots. Based on further research it can be concluded that: (1) The ecophysiological responses of the banana plantlets (Musa spp.) to Cr stress was indicated by the reduction relative growth rate, the height, the number of leaves and chlorophyll content with increase concentrations of Cr in the medium; The ecophysiological responses of the PT banana plantlets to Cr stress was indicated by the growth rate, the height, the number of leaves and chlorophyll content was higher than the NPT banana plantlets, (2) Banana plantlets cultivars Ambon Lumut and cultivars Nangka were categorized into a Very High Cr Hyperaccumulator, (3) Antioxidative defense mechanism of banana plantlets (Musa spp.) to Cr stress was indicated by proline content in the leaves, the CAT and APX enzymes activity and CAT and APX genes expression that tended to be higher by the increase of Cr concentrations in the medium; Antioxidative defense mechanism of PT banana plantlets to Cr stress was indicated by the content of proline and level of CAT and APX genes expression that tended to be higher, while the CAT enzyme activity at the shoots and APX enzyme activity in the roots was lower than the NPT banana plantlets.